2011
DOI: 10.1016/j.ajpath.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hyperoxia Causes Pulmonary Vascular Disease and Shortens Life Span in Aging Mice

Abstract: Bronchopulmonary dysplasia is a chronic lung disease observed in premature infants requiring oxygen supplementation and ventilation. Although the use of exogenous surfactant and protective ventilation strategies has improved survival, the long-term pulmonary consequences of neonatal hyperoxia are unknown. Here, we investigate whether neonatal hyperoxia alters pulmonary function in aging mice. By 67 weeks of age, mice exposed to 100% oxygen between postnatal days 1 to 4 showed significantly a shortened life spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 56 publications
7
97
0
Order By: Relevance
“…Vascular pruning is also important for development of the retina, and its disruption in preterm infants receiving oxygen therapies causes retinopathy and blindness (51). Vascular pruning might also be responsible for the loss of microvessels seen in aged mice exposed to neonatal hyperoxia (22). Hence, the loss of type II cells observed in adult mice recovering from exposure to neonatal hyperoxia may be caused by the activation of an apoptotic program designed to ensure proper development of the alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular pruning is also important for development of the retina, and its disruption in preterm infants receiving oxygen therapies causes retinopathy and blindness (51). Vascular pruning might also be responsible for the loss of microvessels seen in aged mice exposed to neonatal hyperoxia (22). Hence, the loss of type II cells observed in adult mice recovering from exposure to neonatal hyperoxia may be caused by the activation of an apoptotic program designed to ensure proper development of the alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that 8-week-old adult mice exposed to > 60% oxygen between postnatal day (pnd)0 and pnd4 have enlarged alveoli attributed in part to increased elastin expression and an imbalance in alveolar epithelial type I and II cells (15,20,21). Although vascular changes were not observed at this age, microvessel pruning and rarefaction, cardiac hypertrophy, and reduced survival were observed by 1 year of age (22). Analogous to children born prematurely, young adult mice exposed to hyperoxia as neonates also exhibit an altered host response to influenza A virus infection (21,23,24).…”
mentioning
confidence: 94%
“…s upraphysiological levels of O 2 in neonates may induce prolonged cellular dysfunctions with increasing morbidity (1,2) and mortality (3). Hypoxia and reoxygenation generates higher levels of reactive oxygen species in the newborn lung when performed with supplemental oxygen (4), and DNA oxidation shows a dose-dependent increase in a model of hypoxia and graded fractions of inspired oxygen (FiO 2 ) (5).…”
mentioning
confidence: 99%
“…[82][83][84][85] Although long-term studies of BPD have primarily focused on late abnormalities of airway function, PVD can also persist into childhood and adult life. 79,[86][87][88][89] Tepper and colleagues 88 have reported that infants with even mild BPD have decreased diffusion capacity when corrected for lung volume, in comparison with age-matched term controls, suggesting that BPD infants may have decreased alveolar surface area available for gas exchange. These differences in diffusion capacity for carbon monoxide were also found to persist in children at 11 years of age who had been born extremely preterm, and striking decreases in diffusion capacity can persist in adult survivors of BPD.…”
Section: Pvd In Bpdmentioning
confidence: 99%